БАҲОНИНГ ПРЕДМЕТ ВА БЕЛГИ ЁРДАМИДА ИФОДАЛАНИШИ (Scientific journal of the Fergana State University, 2023)
In this article the idea of reflecting the points with helping of objects and symbols is mentioned.